Laporan Kasus: Nyeri Punggung Bawah Akibat Kerja pada Pekerja Pemanen Sawit - Winda Trijayanthi Utama; Salsabila Nurislami (CV. Jasa Sukses Abadi, 2026)
Work-related diseases in the agricultural sector have shown a rising trend in recent years. Heavy physical activities involving non-ergonomic postures, heavy lifting, and repetitive movements increase the risk of injuries and musculoskeletal disorders. Low back pain is one of the most common musculoskeletal complaints among workers in this sector. This case report aims to analyze low back pain in an oil palm harvester using the application of the seven-step occupational diagnostic approach. The seven-step occupational diagnosis was applied to determine the causal relationship between occupational exposure and the patient’s symptoms. Clinical diagnosis and management were conducted in accordance with clinical guidelines.The patient was an oil palm harvester with recurrent episodes of low back pain. Occupational analysis showed that the patient worked in prolonged non-ergonomic postures—standing with neck extension, frequent forward bending, and repetitive heavy lifting—for 15 years, with daily work durations of 8–10 hours. Based on the seven-step occupational diagnostic assessment, the patient’s condition was classified as an occupational disease. Management included pharmacological therapy and ergonomic education. This case highlights that non-ergonomic working postures, the use of non-ergonomic tools, repetitive movements, and heavy lifting significantly contribute to the development of low back pain among agricultural workers. Pharmacological treatment must be accompanied by preventive strategies through ergonomic education. This case report underscores the importance of physicians’ competency in establishing occupational diagnoses and providing comprehensive management for workers with occupational diseases